Differential Activity of PARP Inhibitors in BRCA1- Versus BRCA2-Altered Metastatic Castration-Resistant Prostate Cancer. (2021) - Taza, Fadi; Holler, Albert E.; Fu, Wei; Wang, Hao; Adra, Nabil; Albany, Costantine; Ashkar, Ryan; Cheng, Heather H.; Sokolova, Alexandra O.; Agarwal, Neeraj; Kessel, Adam; Bryce, Alan; et al.
Abstract : PURPOSE: Two poly (ADP-ribose) polymerase (PARP) inhibitors (olaparib and rucaparib) are US Food and Drug Administration–approved for patients with metastatic castration-resistant prostate cancer (mCRPC) harboring BRCA1 / 2 mutations, but the relative efficacy of PARP inhibition in BRCA1 - versus BRCA2 -altered mCRPC is understudied. METHODS: We conducted a multicenter retrospective analysis involving 12 sites. We collected genomic and clinical data from 123 patients with BRCA1 / 2 -altered mCRPC who were treated with PARP inhibitors. The primary efficacy end point was the prostate-specific antigen (PSA) response (≥ 50% PSA decline) rate. Secondary end points were PSA progression-free survival (PSA-PFS), clinical or radiographic PFS, and overall survival. We compared clinical outcomes, and other genomic characteristics, among BRCA1 - versus BRCA2 -altered mCRPC. RESULTS: A total of 123 patients (13 BRCA1 and 110 BRCA2 ) were included. PARP inhibitors used were olaparib (n = 116), rucaparib (n = 3), talazoparib (n = 2), and veliparib (n = 2). At diagnosis, 72% of patients had Gleason 8-10 disease. BRCA1 patients were more likely to have metastatic disease at presentation (69% v 37%; P = .04). Age, baseline PSA, metastatic distribution, and types of previous systemic therapies were similar between groups. There were equal proportions of germline mutations (51% v 46%; P = .78) in both groups. BRCA1 patients had more monoallelic (56% v 41%; P = .49) and concurrent TP53 (55% v 36%; P = .32) mutations. PSA50 responses in BRCA1 - versus BRCA2 -altered patients were 23% versus 63%, respectively ( P = .01). BRCA2 patients achieved longer PSA-PFS (HR, 1.94; 95% CI, 0.92 to 4.09; P = .08), PFS (HR, 2.08; 95% CI, 0.99 to 4.40; P = .05), and overall survival (HR, 3.01; 95% CI, 1.32 to 6.83; P = .008). Biallelic (compared with monoallelic) mutations, truncating (compared with missense) mutations, and absence of a concurrent TP53 mutation were associated with PARP inhibitor sensitivity. CONCLUSION: PARP inhibitor efficacy is diminished in BRCA1 - versus BRCA2 -altered mCRPC. This is not due to an imbalance in germline mutations but might be related to more monoallelic mutations and/or concurrent TP53 alterations in the BRCA1 group.